PROSES PEMILIHAN SAMPAH PLASTIK SECARA KREATIF DI DESA SUKAHARJA KECAMATAN CIOMAS - Rizqina Dwitasari Junaedy; Syaiful Syaiful; Asri Kusuma Wardhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2026)
The largest source of waste comes from residential areas, the composition is 75% organic waste and only 25% inorganic waste. Organic waste has been widely used as a material for making compost, briquettes and biogas, but inorganic waste is still very minimally managed. The most inorganic waste found in society is plastic waste. In 2008, the production of plastic waste for packaging was 925,000 tons and around 80% of it has the potential to become waste that is hazardous to the environment. Because of its large potential, it would be better to utilize this plastic waste into creative products and services in order to manage plastic waste properly, so that plastic really supports our lives. As a creative product, plastic waste creations have promising commercial value. This product has a selling power that can generate profits. In general, this business is divided into two types, namely products and services.